EFFECT OF DIGITALIZATION ON THE LEVEL OF TAX COMPLIANCE FOR COMPANIES - Puholovko , I. S. (The actual problems of regional economy development, 2024)
The article is focused on topical issues of tax compliance and the study of the effect of digitalization of interaction on tax reporting. The article describes the changes in tax relations caused by the development of information technology and the potential challenges inherent in these processes. Special focus is made on the fact that digitalization can not only change business fundamentally, but tax authorities can also take advantage of this transforming environment. The author substantiates the patterns of changes in tax relations determined by the development of information technology and assesses the challenges that these processes entail. It is noted that the definition of tax compliance is planned to be regulated in Ukrainian tax legislation. The author confirms the position that digitalization in itself is not the main condition for improving the level of tax compliance of business, since in each country there are other obstacles that allow for non-compliance with tax obligations - business practices, tax culture, weakness of state institutions, lack of the rule of law. Overcoming these problems requires a certain level of innovation on the part of regulatory authorities. The article analyzes the general state of openness of data in the EU countries and highlights Ukraine's leading positions in the field of open data. Presented as an example of information overlap between the planned information to be submitted after the introduction of the Standard Audit File for Tax Purposes (SAF-T) and the existing tax reporting in electronic form. Particular attention is focused on the possibility of such a factor as excessive or redundant compliance, which can become a significant demotivator for building quality interaction between large taxpayers and the state. The author emphasizes that successful implementation of innovative methods of interaction requires a better understanding of the driving forces of compliance behavior. It is determined that for the successful transformation of tax relations between business and the government, it is not enough to transfer reporting into electronic format, as this may have a rather limited actual effect on the parties. The existence of electronic services makes it easier for taxpayers to interact online. At the same time, electronic reporting does not affect taxpayers' compliance with tax laws.